Validation of the Chinese Cultural Tightness–Looseness Scale and General Tightness–Looseness Scale - Leng, Jie; Ma, Hang; Lv, Xiaojun; Hu, Ping (Frontiers in Psychology, 2023)
Introduction: This study aims to revise the Cultural Tightness-Looseness Scale (CTLS) and General Tightness-Looseness Scale (GTLS), and explore the group heterogeneity of tightness-looseness perception in Chinese populations. Methods: Sample 1 (n = 2,388) was used for item analysis and exploratory factor analysis, and sample 2 (n = 2,385) was used for confirmatory factor analysis and latent profile analysis. Sample 3 (n = 512) was used for the reliability test and criterion validity test, among which 162 participants were used for the test-retest reliability examination after a four-week interval. Measurements included the CTLS, GTLS, International Personality Item Pool, Personal Need for Structure Scale, and Campbell Index of Well-Being. Results: The revised CTLS contained four items and retained a single-dimensional structure. The revised GTLS consisted of eight items divided into two dimensions: Compliance with Norms and Social Sanctions. Latent profile analysis extracted two profiles on both CTLS and GTLS scores, indicating that the sample can be divided into two subgroups: high and low perception of tightness. Discussion: The Chinese versions of the CTLS and GTLS can be used as valid and reliable measures of tightness-looseness perception in a Chinese population.